2014
DOI: 10.1111/cei.12359
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated histones contribute to the immunostimulatory potential of neutrophil extracellular traps in systemic lupus erythematosus

Abstract: Original ArticleAcetylated histones contribute to the immunostimulatory potential of neutrophil extracellular traps in systemic lupus erythematosus OTHER ARTICLES PUBLISHED IN THIS SERIESDying autologous cells as instructors of the immune system. Clinical and Experimental Immunology 2015, 179: 1-4. Anti-dsDNA antibodies as a classification criterion and a diagnostic marker for systemic lupus erythematosus: critical remarks. Clinical and Experimental Immunology 2015, 179: 5-10. The effect of cell death in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 26 publications
2
80
0
Order By: Relevance
“…Notably, in contrast to our experience in murine LN kidneys, a reliable staining of human LN biopsies for citrullinated histone H3 could not be obtained (data not shown). Stainings with monoclonal antibodies KM-2 (against triacetylated histone H4 [K8, 12,16] Notably, these histone modifications were previously shown to be enriched in NETs when compared with unstimulated neutrophils. 12 Taken all stainings together, the glomerular presence of NETs could be identified in 7 of the 8 renal biopsies, ranging from 18% to 75% NET-positive glomeruli.…”
Section: Glomerular Nets Are Associated With Proteinuria and Endmt Inmentioning
confidence: 99%
“…Notably, in contrast to our experience in murine LN kidneys, a reliable staining of human LN biopsies for citrullinated histone H3 could not be obtained (data not shown). Stainings with monoclonal antibodies KM-2 (against triacetylated histone H4 [K8, 12,16] Notably, these histone modifications were previously shown to be enriched in NETs when compared with unstimulated neutrophils. 12 Taken all stainings together, the glomerular presence of NETs could be identified in 7 of the 8 renal biopsies, ranging from 18% to 75% NET-positive glomeruli.…”
Section: Glomerular Nets Are Associated With Proteinuria and Endmt Inmentioning
confidence: 99%
“…Various post-translational modifications of cellular proteins occur during NETosis and the enhanced externalization of these proteins, combined with defective clearance, may promote disruptions in adaptive immunity that further drive SLE pathogenesis (117, 119, 120, 203). SLE NETs contain histone modifications that are also observed during apoptosis (203).…”
Section: Netosis-derived Post-translational Modifications In Slementioning
confidence: 99%
“…The results indicated that the modifications of histones are involved in the pathogenesis of SLE (25,26). Acetylated histones contribute to the immunostimulatory potential of neutrophil extracellular traps (NETs) in systemic lupus erythematosus (27). It was found that the histone acetyltransferases (HATs) and histone deacetylases (HDACs) were abnormal in patients with active SLE (25).…”
Section: Histone Modifications and Slementioning
confidence: 99%